"Digital Era": Impact on the Economy and the Education System (Country Analysis) - GAPSALAMOV, A.R; AKHMETSHIN, E.M; BOCHKAREVA, T.N; VASILEV, V.L (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents the results of a historiographic analysis of the work on the implementation and use of digital technologies in the national education systems of the world’s leading countries. The aim of study was to identify difficulties in the implementation of digital technologies in a national education system and directions for their improvement. The research allowed to conclude that the introduction of digitalization in the national education system generates new difficulties, such as the lack of understanding of the ongoing processes, insufficient funding, etc. However, countries can enter a new level of economy digitalization only with targeted government support.RESUMEN El artículo presenta los resultados de un análisis historiográfico del trabajo sobre la implementación y el uso de tecnologías digitales en los sistemas educativos nacionales de los principales países del mundo. El objetivo del estudio fue identificar dificultades en la implementación de tecnologías digitales en un sistema educativo nacional y las instrucciones para su mejora. La investigación permitió concluir que la introducción de la digitalización en el sistema educativo nacional genera nuevas dificultades, como la falta de comprensión de los procesos en curso, fondos insuficientes, etc. Sin embargo, los países pueden ingresar a un nuevo nivel de digitalización de la economía solo con apoyo de un gobierno específico.